Management Analysis Of Medicine Management During The Covid19 Pandemic At Simpang Jaya Health Center, Tadu Raya District, Nagan Raya District - Marzeliana Marzeliana (Lembaga Pengembangan Kinerja Dosen, 2024)
Management Drug management consists of Planning, Procurement, Receiving, Storage, Distribution, Destruction, Control. During the Covid 19 pandemic, demand for medicines in the world increased to USD 4.5 billion, for this reason it is necessary to carry out good medicine management. This research uses a qualitative research method with a case study approach. The informants in this research were the Head of the Community Health Center, Head of the Medicine Warehouse, Medicine Warehouse Installation Staff, and Health Installation Staff at Simpang Jaya Health Center, Tadu Raya District, Nagan Raya Regency and from triangulated data. This research was conducted from February to October 2021, data collection was carried out by means of in-depth interviews and questionnaires. Data analysis by identifying problems using a fishbone diagram to obtain cause and effect relationships. The results of this research show that expert professions in drug management are very necessary, in order to achieve drug management in accordance with the Minister of Health's Regulation, the lack of cupboards is also an obstacle in drug management, the lack of facilities and infrastructure in the Puskesmas includes electronic devices such as computers so that the recording and reporting of drugs is still manually. It is recommended that the implementation of drug management based on the Minister of Health's Regulation concerning Standard Technical Instructions for Public Health Center Pharmaceutical Services in 2019 be maintained.